Analisis Unsur Intrinsik Cerpen Laki-Laki Sejati Karya Putu Wijaya - Yuda Saputra; Wini Yuniar Pusparani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The short story Laki Sejati by Putu Wijaya is one of the works of Indonesian literature that depicts the dynamics of human life and internal conflicts. This research aims to analyze the intrinsic elements in the short story, including themes, characters and characterization, plot, setting, point of view, and mandate. Through this analysis, it is revealed how these intrinsic elements are used by the author to build a story that is evocative and full of meaning. The results of the analysis show that the main theme of this short story is the search for identity and the true meaning of